Risk management in the conditions of war - Antoniuk, Nataliia; Антонюк, Наталія (Вежа-Друк, 2023)
Ukraine is one of the richest in natural resources countries of the Eurasian region, has a favourable geographical and geopolitical position is a potential transit corridor for energy and commodity flows between the East and West. Ukraine is one of the leading countries in the world in terms of explored reserves of iron, manganese, titanium-zirconium ores, coal, graphite, kaolin, sulphur. However, according to the World Bank estimates, the Ukrainian economy, which is largely focused on the export of low value-added products, is not efficient enough and therefore, in terms of gross national income per capita, the country is included in the group of countries with lower middle-income. From the beginning of the war, active battles were fought in regions that generated up to 60% of GDP, which created negative consequences for the entire territory of the state. The Ukrainian economy lost almost 100 billion USD, according to forecasts of the National Bank of Ukraine, GDP may fall by 40–45% annually, the main share of which is traditionally created by the agricultural sector (approximately 35–40%), its importance in terms of the national economy has also been shown the above study.
Управління ризиками в умовах війни
Україна є однією з найбагатших на природні ресурси країн Євразійського регіону, має вигідне географічне та геополітичне положення, є потенційним транзитним коридором для енергетичних і товарних потоків між Сходом і Заходом. За розвіданими запасами залізних, марганцевих, титано-цирконієвих руд, вугілля, графіту, каоліну, сірки Україна посідає одне з провідних місць у світі. Проте, за оцінками Світового банку, українська економіка, здебільшого орієнтована на експорт продукції з низькою доданою вартістю, недостатньо ефективна, тому за рівнем валового національного доходу на душу населення країна входить до групи країн із рівнем доходу нижче середнього. З початку війни велися активні бої в регіонах, які створювали до 60% ВВП, що створило негативні наслідки для всієї території держави. Українська економіка втратила майже 100 млрд доларів США, за прогнозами НБУ, ВВП може падати на 40–45% щорічно, основну частку якого традиційно створює аграрний сектор (приблизно 35–40%), його Важливість з точки зору національної економіки також показала наведене дослідження.
Keywords: risk management; national economy; sustainable ecological, economic and social development; 338.984